Durability of graphite coated carbon composite bipolar plates for vanadium redox flow batteries. (15th December 2015) - Choe, Jaeheon; Lim, Jun Woo; Kim, Minkook; Kim, Jinwhan; Lee, Dai Gil
Abstract: Composite bipolar plates for vanadium redox flow batteries (VRFBs) and fuel cells are coated with expanded graphite to decrease the interfacial contact resistance of the carbon composite. The bipolar plates of vanadium redox flow batteries are exposed to electro-chemical corrosion, which might degrade the graphite coating layer. From two types of graphite foil, i.e., pyrolytic graphite and expanded flake-type graphite, the former has higher durability because its graphene sheets are crystallized in a planar direction with a highly oriented structure, which has a stronger van der Waals bonding. In this study, the characteristics of the pyrolytic graphite and expanded flake-type graphite are investigated with respect to the porosity of graphite. The durability of the graphite coating of the carbon/epoxy composite bipolar plate during the electrochemical reaction in vanadium electrolytes, based on highly concentrated sulfuric acid, is investigated. The areal specific resistances (ASRs) of the bipolar plates coated with pyrolytic graphite are measured, from which the ASR is expressed in terms of modulus of the graphite based on the Hertzian contact model. A single cell test is performed to evaluate the performance of the developed bipolar plate.